Self-care interventions for advancing sexual and reproductive health and rights – implementation considerations - Manjulaa Narasimhan; Carmen H. Logie; James Hargreaves; Wendy Janssens; Mandip Aujla; Petrus Steyn; Erica van der Sijpt; Anita Hardon (Journal of Global Health Reports)
Self-care refers to the ability of people to promote their own health, prevent disease, maintain health, and cope with illness and disability, with or without the support of a health or care worker. Self-care interventions are tools that support self-care as additional options to facility-based care. Recognizing laypersons as active agents in their own health care, the World Health Organization (WHO)’s global normative guideline on self-care interventions recommends people-centred, holistic approaches to health and well-being for sexual and reproductive health and rights. Examples of such interventions include pregnancy self-testing, self-monitoring of blood glucose and/or blood pressure during pregnancy and self-administration of injectable contraception. Building on previous studies and aligning with the WHO classification for self-care, we discuss nine key implementation considerations: agency, information, availability, utilization, social support, accessibility, acceptability, affordability, and quality. The implementation considerations form the foundation of a model implementation framework that was developed using an ecological health systems approach to support sustainable changes in health care delivery.